Anomaly Detection in Imbalance Secure Water Treatment Dataset Using LSTM-DC-Wasserstein Generative Adversarial Network with Gradient Penalty - Kevin, Jonathan Marshell; Raharya, Naufan (Universitas Indonesia, 2024)
In modern industrial systems, particularly with the advancement of the Internet of Things (IoT), industry players can record machine and system data for comprehensive analysis. This capability is crucial for detecting anomalies and taking necessary corrective actions.However, it is common for manufacturers to lack recorded anomaly datasets, especially for newly operational systems. In this paper, we develop a model to detect anomalies in an imbalanced dataset from the Secure Water Treatment (SWaT) system. The performance of the proposed model is compared with previous works, demonstrating significant improvements in anomaly detection capabilities where it achieves accuracy of 0.9546, precision of 0.9086, recall of 0.6654, and F1 score of 0.7681